2004
DOI: 10.1177/154405910408301206
|View full text |Cite
|
Sign up to set email alerts
|

Local OPG Gene Transfer to Periodontal Tissue Inhibits Orthodontic Tooth Movement

Abstract: Previously, we discovered that RANKL expression is induced in compressed periodontal ligament cells, and that this promotes osteoclastogenesis on the compression side in orthodontic tooth movement. We hypothesized that local OPG gene transfer to the periodontium would neutralize the RANKL activity induced by mechanical compressive force, thereby inhibiting osteoclastogenesis and diminishing tooth movement. The upper first molars of six-week-old male Wistar rats were moved palatally by means of a fixed-orthodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 28 publications
3
99
2
5
Order By: Relevance
“…Another focus of research is OPG (osteoprotegerin), a decoy receptor that competes with RANKL to bind RANK, which when bound leads to suppression of osteoclast differentiation and activation, also inducing apoptosis. OPG gene transfer to the PDL was shown to inhibit tooth movement and osteoclast differentiation (Kanzaki et al, 2006;Kanzaki et al, 2004;. Although PGE1 seems to increase the rate of tooth movement and root resorption (Lee, 1990;Spielmann, Wieslander & Hefti, 1989;Yamasaki, Shibasaki & Fukuhara, 1983;Yamasaki et al, 1984;Zhang, 1992), some of the PGE2 effects in orthodontics are still controversial.…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…Another focus of research is OPG (osteoprotegerin), a decoy receptor that competes with RANKL to bind RANK, which when bound leads to suppression of osteoclast differentiation and activation, also inducing apoptosis. OPG gene transfer to the PDL was shown to inhibit tooth movement and osteoclast differentiation (Kanzaki et al, 2006;Kanzaki et al, 2004;. Although PGE1 seems to increase the rate of tooth movement and root resorption (Lee, 1990;Spielmann, Wieslander & Hefti, 1989;Yamasaki, Shibasaki & Fukuhara, 1983;Yamasaki et al, 1984;Zhang, 1992), some of the PGE2 effects in orthodontics are still controversial.…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…16 Therefore, local RANKL gene transfer could induce RANKL protein production not only in the palatal side of M1 but also all around M1. Local RANKL gene transfer significantly induced the osteoclastogenesis not only in the compressed area of the periodontium, but also in other areas of the periodontium (Figures 6a-d).…”
Section: Rankl Gene Transfer Induces Tmmentioning
confidence: 99%
“…The standardized compressive spring (Figure 1a) was used for moving the teeth. 16 Cloning of the mouse RANKL gene and construction of the RANKL expression plasmid Total RNA was extracted from the mouse osteoblastic cell-line MC3T3-E1 and then reverse transcribed. Firststrand cDNA was subjected to PCR amplification using specific PCR primers, designed using mouse RANKL cDNA plus restriction site, primer XhoI site+RANKL-upstream (5 0 -GGGCTCGAGATGCCTGAGGCCCAGCC ATTTGC-3 0 ) and primer RANKL-downstream+XbaI site (5 0 -CTAGTCTAGAACAGCCCAGTGACCATTC-3 0 ).…”
Section: Animals and Orthodontic Appliancementioning
confidence: 99%
See 1 more Smart Citation
“…RANKL promotes the formation and bone resorptive activity of osteoclasts, the specialized cells charged with bone resorption (Hofbauer and Heufelder, 2001). Conversely, inhibitors of osteoclast formation and activity including osteoprotegerin (OPG), integrin inhibitors, bisphosphonates and inhibitors of matrix metalloproteinases all slowed tooth movement Dolce et al, 2003;Kanzaki et al, 2004;Dunn et al, 2007). Although these studies showed that it is possible to manipulate the speed at which orthodontic tooth movement proceeds by altering osteoclast activity, the specific agents tested to date are probably inappropriate for orthodontic use in the clinic as there would be too much danger of off target effects.…”
Section: Introductionmentioning
confidence: 99%